Chemical constituents of Cinnamomum iners (Lauraceae) - 463265 Rohanis Hasan; Shajarahtunnur Jamil, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007